2014
DOI: 10.1136/bjophthalmol-2014-305361
|View full text |Cite
|
Sign up to set email alerts
|

Ganglion cell and inner plexiform layer thickness determined by spectral domain optical coherence tomography in patients with brain lesions

Abstract: Our results suggest that various kinds of brain lesions with different locations show considerable reduction in GCIPL thickness. Thickness of the GCIPL performed better than conventional pRNFL thickness for the diagnosis of retinal ganglion cell damage induced by brains lesions. The pattern of GCIPL loss may be of particular usefulness in recognising a potential intracranial lesion in cases suspected of having normal-tension glaucoma. GCIPL thickness determined by OCT can be an early and useful marker to estim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
21
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 24 publications
2
21
0
Order By: Relevance
“…Importantly, it may represent the maximum limit that can be damaged by EMB toxicity. Our results also support the idea that minimum mGCIPL thickness has the best capability in the diagnosis of RGC-related diseases as well as EON 11. In the present study, the average value of minimum mGCIPL in patients with EON was 64.0 µm, which was comparable with findings in other studies.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Importantly, it may represent the maximum limit that can be damaged by EMB toxicity. Our results also support the idea that minimum mGCIPL thickness has the best capability in the diagnosis of RGC-related diseases as well as EON 11. In the present study, the average value of minimum mGCIPL in patients with EON was 64.0 µm, which was comparable with findings in other studies.…”
Section: Discussionsupporting
confidence: 92%
“…Medeiros et al 27 demonstrated that the substantial loss of RGCs is already present and observable in glaucomatous eyes with the earliest detectable VF loss on automated perimetry. In addition, Moon et al 11 reported that mGCIPL thickness might be an earlier indicator of damage in the visual pathway as compared with VF assessment. Thus, VF results may not exactly reflect RGC damage and therefore might not be employed as a useful marker to determine EMB toxicity in early EON.…”
Section: Discussionmentioning
confidence: 99%
“…11,21,22 Furthermore, recent studies demonstrated RNFL loss in patients with occipital lobe lesions 14 and after acquired lesions of the brain even in areas other than the occipital lobe 15,16 through the process of retrograde transsynaptic degenerations of neurons. [14][15][16] This is interesting as we studied adult patients with NF1 with no history of OPG and found thinning of the mean pRNFL (P = 0.003), RNFL (P = 0.022), and GCL-ILP (P , 0.001) layers reflecting axonal and neuronal loss. It is known that NF1 is characterized by aberrant proliferation of multiple tissues of neural crest origin.…”
Section: Discussionmentioning
confidence: 98%
“…The recent advent of segmentation measurements has led to retinal layer thickness evaluation in various pathologies affecting the RNFL. Thinning of the ganglion cell layer was demonstrated in multiple sclerosis, neuromyelitis optica, and in patients with brain lesions [11][12][13][14][15][16] ; thus, some authors suggested that ganglion cell layer-inner plexiform layer (GCL-IPL) may potentially serve as a structural marker of disease. 11 Gu et al 17 demonstrated GCL-IPL loss in young children with OPG secondary to NF1 and suggested that GCL-IPL is a more accurate and reliable biomarker of vision than pRNFL, as it is not hampered by axonal swelling, axonal atrophy, and blood vessel artifacts within the pRNFL.…”
mentioning
confidence: 98%
“…25 Thinning of the papillomacular bundle has also been reported in neurologic and neuro-ophthalmologic disorders as a sign of neurodegeneration. 33,34 It is also widely recognized that neurodegeneration participates in early microvascular changes that occur in DR such as the breakdown of the blood-retinal barrier, 35,36 vasoregression, 37 and impairment of neurovascular coupling. 38 Various neuroprotective agents have been shown in animal models of DR to reduce RGC apoptosis.…”
Section: Discussionmentioning
confidence: 99%